User testing for serious game design: improving the player experience - Shaw, Ross W.; Sperano, Isabelle; Andruchow, Robert; Cobzas, Dana (My University, 2022)
This case study reflects on our use of user testing during a research project in which we designed a serious video game, “Life on the Edge.” The target audience of the game is first-year post-secondary biology students. As we designed the game, user testing was a critical component that allowed us to identify issues. Any issues that interfere with the flow or enjoyment of a video game can be distracting to players. In what follows, we will describe the research design and discuss the processes for testing a serious video game that will allow you to identify game issues successfully. How you recruit participants, test players, and prioritize player feedback is a component of effective user testing and improving your game. With user testing, we were able to identify problems in the game, prioritize them, and address them. By using variable user testing methods, you can adapt to the changing needs of your game project and develop a successful serious video game.
Keywords: biological sciences; facilitators; feedback; game playing; games; gaming; observer; prototypes; students; video games